Measuring the health-related quality of life in young children: how far have we come?. Issue 1 (1st January 2019) - Germain, Nicola; Aballéa, Samuel; Toumi, Mondher
ABSTRACT: The importance of understanding the impact of disease and treatment on children's Health-Related Quality of Life (HRQoL) has given rise to an increasing use of child self-report and observer or proxy instruments. In this article, we review the status quo and challenges of HRQoL measurement specific to children under five. A number of HRQoL questionnaires exist for use with children and/or proxies, and both guidelines and reviews have been published on paediatric HRQoL. However, none address the challenges of measurement for children under five, for whom proxy measures should be used. In reality, there is significant heterogeneity in the cut-off age for self-report questionnaires. Recommendations are that proxies should be used for observable concepts, but not for concepts that require interpretation. Some research has been undertaken on dimensions/concepts in paediatric HRQoL questionnaires. However, no HRQoL models have been developed specifically for children, and heterogeneity in questionnaire dimensions underlines that there is no clear grasp of what HRQoL means in paediatric populations. There is a need to carry out research in order to develop theoretical models of HRQoL that are specific to children at different developmental stages, in order to evaluate and support new and existing measures for paediatric HRQoL and their use in clinical practice as well as clinical trials.